1994
DOI: 10.1111/j.1365-2621.1994.tb08152.x
|View full text |Cite
|
Sign up to set email alerts
|

Screw Configuration Effects on Corn Starch Expansion During Extrusion

Abstract: Normal corn starch was extrusion cooked in a Brabender single-screw extruder. Three screws with no mixing, one mixing or two mixing elements were used to extrude the samples through a 3 mm cylindrical die nozzle at 140°C barrel temperature and 140 'pm screw speed. Dependent variables included overall and radial expansion ratios, bulk density and specific mechanical energy (SME). Extrudates were ground and re-extruded using the same three screws, and the same extrusion conditions. Significant differences (P > 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…This result indicates that higher treatment temperature (75°C and 95°C) is needed to reduce the moisture content of WPC80 to approximately 36%. For example, several studies have been conducted on the effect of moisture content on extrudate properties for starches and proteinbased feed materials [23][24][25][26][27][28][29][30]. In all these studies, the authors found a correlation between moisture loss and structural changes for both starches and protein-based products which agrees with these results for torque and SME for CM and WPC80.…”
Section: Resultssupporting
confidence: 64%
“…This result indicates that higher treatment temperature (75°C and 95°C) is needed to reduce the moisture content of WPC80 to approximately 36%. For example, several studies have been conducted on the effect of moisture content on extrudate properties for starches and proteinbased feed materials [23][24][25][26][27][28][29][30]. In all these studies, the authors found a correlation between moisture loss and structural changes for both starches and protein-based products which agrees with these results for torque and SME for CM and WPC80.…”
Section: Resultssupporting
confidence: 64%
“…Density and expansion ratio (according to Sokhey, Kollengode, & Hanna, 1994). Determination of density was performed by rapeseed displacement using extrudate sticks of mass approximately 5 g; expansion ratio was measured by average extrudate diameter (10 measurements for 10 various sticks).…”
Section: Physical Properties Of Extrudatesmentioning
confidence: 99%
“…Expansion is mainly governed by the sudden decrease in pressure attheat the die section, which results in water phase transition and formation of air cells in the extrudates (Alves et al, 1999;Lam & Flores 2003;Moore, 1990;Chevanan et al, 2007a).Additionally, during the cooking process, the melted dough exhibits a pseudoplastic behavior and thus, a substantial decrease in the apparent viscosity of the dough, which is influenced by the temperature, moisture content and type of the ingredients and ultimately affects the extent of pressure release and expansion of the finished product (Rosentrater et al, 2005;Chevanan et al, 2007a). In general, the more moisture, the less expansion due to the lubricant effect of water and consequent decrease in apparent viscosity of the dough (Mjoun & Rosentrater, 2011); the higher the starch content, the greater the expansion due to starch gelatinization and elastic behaviour of the dough inside the barrel and consequent pressure rise at the die exit (Nielsen, 1976;Kokini et al, 1992;Case et al, 1992;Sokhey et al, 1994;Ibanoglu et al, 1996). Kim et al (1989) suggested that increasing the extent of expansion as a result of increase in barrel temperature could be related to more starch gelatinization and more excretion of super-heated steam.…”
Section: Expansion Ratio (Er)mentioning
confidence: 99%